2022
DOI: 10.1186/s12889-022-13660-5
|View full text |Cite
|
Sign up to set email alerts
|

How does mode of delivery associate with double burden of malnutrition among mother–child dyads?: a trend analysis using Bangladesh demographic health surveys

Abstract: Background The simultaneity of undernourishment among child and overweight/obesity among mothers in lower-and-middle-income-countries (LMICs) introduces a new nutrition dilemma, known as double burden of malnutrition (DBM). Amidst of such paradox, the hike of caesarean section (CS) delivery is also triggering child undernutrition and maternal obesity. A gap of knowledge regarding the effect of mode of delivery on DBM still persists. The study aims to explore the association between DBM at house… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…However, Studies done by (Senthilkumar SK et al, 2018)of Fogera District, Northwest Ethiopia has shown that under-five children who are appropriately immunized for age were protected against under nutrition. But There is need for modern studies of nutritional immunology, selecting populations of children based on current definitions of undernutrition was reported by (Prendergast, n.d.).A large proportion of healthy children were delivered baby by Cesarian section method, it mean there is significant association between Cesarian section delivery and malnutrition, however this result incompatible with (Saaka & Hammond, 2020) who reported there was no significant association between caesarean delivery and the other growth indicators, furthermore according to (Sutopa & Bari, 2022) there is strong association between double burden of malnutrition and mode of delivery, children born by CS delivery are more associated with DBM than the children born by normal delivery. A further possible explanation for the controversy could be that in this study we only included those children who their weight should be between 2500-4500 gram at time of delivery and pregnancy period of mother should be between 37-40 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…However, Studies done by (Senthilkumar SK et al, 2018)of Fogera District, Northwest Ethiopia has shown that under-five children who are appropriately immunized for age were protected against under nutrition. But There is need for modern studies of nutritional immunology, selecting populations of children based on current definitions of undernutrition was reported by (Prendergast, n.d.).A large proportion of healthy children were delivered baby by Cesarian section method, it mean there is significant association between Cesarian section delivery and malnutrition, however this result incompatible with (Saaka & Hammond, 2020) who reported there was no significant association between caesarean delivery and the other growth indicators, furthermore according to (Sutopa & Bari, 2022) there is strong association between double burden of malnutrition and mode of delivery, children born by CS delivery are more associated with DBM than the children born by normal delivery. A further possible explanation for the controversy could be that in this study we only included those children who their weight should be between 2500-4500 gram at time of delivery and pregnancy period of mother should be between 37-40 weeks.…”
Section: Discussionmentioning
confidence: 99%